2022
DOI: 10.1088/2631-6331/ac5466
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and modelling of the fracture inhibition potential of heat treated doum palm nut fibres in phenolic resin matrix polymer composite: a Taguchi approach

Abstract: The chemical treatment of natural fibres for its surface modification for the development of polymer composites is popular but it comes with an adverse effect of a chemical change of the fibres. In this study, the surface modification of natural fibres (doum palm nut fibres) with low-temperature heat treatment (30℃-75℃) has been reported as an alternative method to the treatment of natural fibres for the development of polymer composites. Taguchi method of the design of experiment was employed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The regression analysis produced a predictive mathematical model for the percentage elongation (PE) as a function of the stir casting process parameters that gave a high level of prediction, with R-Square, R-Square (adj) and R-Square (pred) values of 91.60%, 87.41%, and 79.32%, respectively. According to 55 , 56 , an R-Square value greater than 75% is deemed adequate, implying a good fit between the responses and the process parameters. The regression model is given in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The regression analysis produced a predictive mathematical model for the percentage elongation (PE) as a function of the stir casting process parameters that gave a high level of prediction, with R-Square, R-Square (adj) and R-Square (pred) values of 91.60%, 87.41%, and 79.32%, respectively. According to 55 , 56 , an R-Square value greater than 75% is deemed adequate, implying a good fit between the responses and the process parameters. The regression model is given in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Another major drawback is their hazardous nature during processing which makes them injurious to health. Recently, research focus has been shifting more to the exploration of the natural fiber reinforced composites from the traditional monolithic materials (Samuel et al, 2022a;Samuel et al, 2022b;Alabi et al, 2022;Samuel et al, 2022c;Samuel et al, 2022d). The composition of composite materials constituents (e.g., polymers and fibers) used for the development of wind turbine blades are usually varied to achieve improved performance or properties.…”
Section: Current Materials For Wind Turbine Blade Manufacturementioning
confidence: 99%
“…The model indicated that check time, decision time, and delivery time were the main factors influencing downtime, rather than the actual maintenance time. This shows that there is the need for the optimization of not only the process of patients access to the machines but also the availability (Samuel et al, 2022a;Samuel et al, 2022b;Alabi et al, 2022). The purpose of this study is to assess the management and maintenance of external beam linear accelerators and cobalt 60 radiotherapy machines in Nigeria.…”
Section: Introductionmentioning
confidence: 99%